Tetragonal Superstructure of the Antiskyrmion Hosting Heusler Compound Mn1.4PtSn - Vir, Praveen; Kumar, Nitesh; Borrmann, Horst; Jamijansuren, Bayardulam; Kreiner, Guido; Shekhar, Chandra; Felser, Claudia (Chemistry of Materials, 2019)
Skyrmions in non-centrosymmetric magnets are vortex-like spin arrangements, viewed as potential candidates for information storage devices. The crystal structure and noncollinear magnetic structure together with magnetic and spin-orbit interactions define the symmetry of the skyrmion structure. We outline the importance of these parameters in the Heusler compound Mn1.4PtSn which hosts antiskyrmions, a vortex-like spin texture related to skyrmions. We overcome the challenge of growing large micro-twin-free single crystals of Mn1.4PtSn, which has proved to be the bottleneck for realizing bulk skyrmionic/antiskyrmionic states in a compound. The use of 5d-transition metal, platinum, together with manganese as constituents in the Heusler compound such as Mn1.4PtSn is a precondition for the noncollinear magnetic structure. Because of the tetragonal inverse Heusler structure, Mn1.4PtSn exhibits large magneto-crystalline anisotropy and D2d symmetry, which are necessary for antiskyrmions. The superstructure in Mn1.4PtSn is induced by Mn-vacancies, which enable a ferromagnetic exchange interaction to occur. Mn1.4PtSn, the first known tetragonal Heusler superstructure compound, opens up a new research direction for properties related to the superstructure in a family containing thousands of compounds.
CRIS-Team Scopus Importer:2022-04-14